Irrigation scheduling of sunflower with drip irrigation system in newly reclaimed land - Berry, A. M.; Sharaf, G. A.; Hassan, Azza.; Sebaee, Ebtsam (2003)
The objective of this work was to study the effect of irrigation scheduling by three methods throughout drip .irrigation systems (suface and subsurfuce) on sunflower yield in sandy soil. A field experiment was conducted during the summer season of 2003 at EL-Bostan Research Station. TI1e irrigation scheduling treatments were, by following the soil tension, plant water stress and water budget technique. The three methods of irrigation scheduling indicted that the irrigation water has to be applied day by day. Seasonal water consumptive use was 450 mm. Average irrigation applied water was 2555.6 m3 /fed and 2569.2 m3/fed by the surface and subsurface systems respectively. The yield was 1418.6 kg/fed and 1458.9 kg/fed respectively. Due to this, insignificant differences were found between the irrigation water applied by the irrigation systems and /hd resulted yield. Whereas; significant differences were found on both the irrigation applied water and yield due to the scheduling methods. Average water use efficiency (WOE) was 0.561 kglm3 and 0.567 kglm3 for surface and subsurface respectively The WUE was not affected significantly by both the irrigation systems and the scheduling methods. Yield response to water followed the quadratic function. This indicated that applying 2827 m3/fed gives the maximum yield of 1534 kg/fed. Average plant height was 127.44 cm and 122.79 cm for both systems respectively. The WUE was decreased by increasing the plant height. Plant head diameter was 17.23 cm and 17.77 cm for both systems respectively. Insignificant effects were found between the plant head diameter due to the irrigation system, but the effects were significant due to the scheduling method. The yield was increased by increasing the plant head diameter and the plant head diameter increased by increasing the irrigation applied water. TI1e analyses proved that water budget method could be fairly used to schedule irrigation with the drip irrigation systems. The bias exists by the method was referred to experimental error or soil evaporation losses and some other parameters not accounted by the method. The applicability of the method was found much better with the subsurface than the surface drip system. The method over predicts actual soil moisture contents with the surface system. Meanwhile, less perdition was observed with subsurface system.
Includes references.
Summary in Arabic.
1
Keywords: Sunflowers -- Irrigation; Irrigation